Emotional Intelligence and Employee Performance in Nepalese Commercial Banks - Joshi Pratap, Rajesh Kumar (KIC International Journal of Social Science and Management, 2024)
The growing complexities of business operations and human behavior have highlighted the need for employees who possess not only high intellectual capabilities but also strong emotional intelligence (EI). This study examines the impact of emotional intelligence on the performance of employees in commercial banks in Nepal. A sample of 400 employees from 10 banks in the Kathmandu Valley was selected through convenience sampling. Employing a descriptive and causal-comparative research design, data were collected via a structured questionnaire and analyzed using correlation, regression, and ANOVA techniques. The findings reveal a significant positive relationship between emotional intelligence—specifically self-awareness, motivation, empathy, and social skills—and employee performance. However, no significant relationship was found between self-regulation and performance. The study underscores the importance of emotional intelligence in enhancing workplace outcomes and recommends further research to explore deeper connections between EI and employee performance within the Nepalese banking sector.